THE EDUCATIONAL ROLE OF THE ARAB FAMILY: CHALLENGES OF CULTURAL GLOBALIZATION - Mohammad Kamel Al Dwakat; Muneer Kamel Al Dwaikat; Yousef Ahmad Alolabi (International Journal of Business and Society, 2023)
The research paper "The Educational Role of the Arab Family: Challenges of Cultural Globalization" delves into the evolving landscape of family education within Arab societies against rapid cultural globalization. In an increasingly interconnected world, family education emerges as a pivotal societal responsibility with the imperative to provide a comprehensive foundation for individuals from all strata of society. This study underscores the vital role of family education as the primary agent in nurturing well-rounded individuals who can adapt to the dynamic changes spurred by globalization. The paper specifically addresses the impact of globalization on social dynamics and relationships, emphasizing its potential to reshape family structures and values. Employing a comprehensive literature review methodology, the research collected and meticulously analyzed pertinent information, subjecting it to rigorous scientific critique. Drawing from sociological insights and previous literature, the study examines how these transformations may conflict with traditional Islamic values and ethos. Ultimately, the research contributes to understanding the complex interplay between family education, cultural globalization, and preserving core societal values, offering insights into how Arab families can navigate these challenges while upholding their cultural identity.